Attitude, Values, Religiosity, and Halal Certification in Halal Food Purchases by Indonesian Muslim Youth - Penny Rahmawaty; Arif Wibowo; Wardana Wardana (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Purchasing buying behavior is influenced by various factors, including personal values, religiosity, and halal certification. Personal values shape individual attitudes, which in turn can affect consumer decisions. In the context of halal products, halal certification serves as a form of assurance and protection for Muslim consumers. This study aims to examine the influence of personal values, religiosity, and halal certification on purchasing behavior, with attitudes toward halal food consumption as a mediating variable. A quantitative descriptive approach was used, with data collected through surveys and analyzed using Structural Equation Modeling (Partial Least Square). The findings show that personal values, religiosity, and halal certification significantly and positively affect purchasing attitudes and behavior among millennial Muslim consumers. However, attitudes were found to have no significant influence on purchasing behavior and did not mediate the relationship between the three independent variables and purchasing behavior. These results suggest that while personal values, religiosity, and certification shape consumer preferences, purchasing behavior may be driven by other direct factors beyond attitudes.